CLINICAL EVALUATION OF ANTI-HYPERGLYCEMIC ACTIVITY OF OCIMUM SANCTUM IN COMPARISON WITH GLIBENCLAMIDE IN THE RAT MODEL OF T2DM - DWIVIDENDRA KUMAR NIM; PRATAP SHANKAR; RAKESH CHAURASIA; BHAUMIC GOEL; RAKESH KUMAR DIXIT (International Journal of Pharma and Bio Sciences, 2013)
India leads the world in total number of diabetic cases with the estimate of 50.8 million adult populations in 2010. Overall predicted increase in number from 2010 to 2030 is 54% at an annual growth of 2.2%, which is nearly twice the annual growth of total world population. Hyperglycemia or high blood sugar is a condition in which an excessive amount of glucose circulates in the blood. Diabetes Mellitus is one such important disease and characterized by chronic hyperglycemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action or both. Ocimum sanctum is a herb and found throughout the India, with several medicinal and religious purposes and for its essential oils and also possesses anti-hyperglycemic activity. Only a very few studies have been done on this plant to establish their antihyperglycemic property. The purpose of this study is to evaluate the anti-hyperglycemic activity of Ocimum sanctum in the rat model of Diabetes Mellitus Type-2.